Comparison of Internal Forces Redistribution and Displacements Subjected to the Dynamic Wind Gusts depending of Point Fixed Glass Connector Model Shape - Kuliński, Krzysztof; Palacz, Przemysław (Periodica Polytechnica Civil Engineering, 2021)
This paper presents an analysis of the redistribution of stresses and displacements in numerical models of various shapes of glass connectors. Two states of dynamic wind gusts were analyzed: the maximum value of suction and the maximum value of wind pressure. For the sake of simplicity, wind gusts were assumed periodically as a sinusoidal function. The model adopts a rectangular glass plate that transmits wind pressure and suction through the point fixed glass connectors. Therefore, single-arm cross connectors were not only subjected to bending stress, but also to torsion. Four different shapes of connectors were analyzed. In the first part of the numerical analysis, T-shaped and C-shaped cross-sections were adopted, and in the next part, both connectors were modified by adding fillet welds to the models. The dynamic numerical analysis was performed using the finite element method in the ADINA program.